1994
DOI: 10.1111/j.1365-2133.1994.tb08590.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of density of follicles on various regions of the face by cyanoacrylate biopsy: correlation with sebum output

Abstract: The density of follicles on various regions of the human face has received scant attention. We used cyanoacrylate follicular biopsies to determine the number of follicles on the forehead, cheek, chin and nose of 12 healthy adult white women. Sebum output was assessed on the same regions by means of Sebutape. The density of follicles and sebum output followed a centrolateral decreasing gradient. There was no correlation between these two parameters. These regional patterns are important for studies of the patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 12 publications
3
62
0
1
Order By: Relevance
“…Such evaluations were made on CFB taken from symmetrical sites of the forehead at the baseline visit as well as after 2, 4 and 6 weeks of treatment. CFB was developed as an extension of skin surface stripping and refers to a non-invasive collection of stratum corneum and follicular material using cyanoacrylate adhesive [16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26]. The follicular casts so sampled from the upper portion of a follicular duct reflect the balance between comedo formation and lysis.…”
Section: Methodsmentioning
confidence: 99%
“…Such evaluations were made on CFB taken from symmetrical sites of the forehead at the baseline visit as well as after 2, 4 and 6 weeks of treatment. CFB was developed as an extension of skin surface stripping and refers to a non-invasive collection of stratum corneum and follicular material using cyanoacrylate adhesive [16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26]. The follicular casts so sampled from the upper portion of a follicular duct reflect the balance between comedo formation and lysis.…”
Section: Methodsmentioning
confidence: 99%
“…The oily appearance commonly found on the ‘T’ zone (forehead, nose and chin) reflects the dominance of these sebaceous follicles. Pagnoni et al [19] found that sebum output and density of follicles followed a centrolateral decreasing gradient, and Lopez et al [20] showed that such a ‘T’-like distribution could indeed be clearly observed even in the women presenting the lowest mean value of sebum casual level 1 . We conclude that all skins are of a ‘combination’ type, with increased sebum values on the ‘T’ zone compared to the rest of the face, regardless if the skin is oily or not.…”
Section: Sebaceous Gland Anatomymentioning
confidence: 99%
“…This represents a noninvasive method which combines the tape stripping technique [22] with cyanoacrylate skin surface biopsies [23,24] . Normally, for a cyanoacrylate skin surface biopsy, superglue is applied onto the skin surface and removed after polymerization together with an unknown amount of corneocytes and follicular casts [23] .…”
Section: Introductionmentioning
confidence: 99%